Growth, Water Relations and Physiological Changes of Young Durian (Durio zibenthinus Murr) as Influenced by Water Availability - Ismail, Mohd Razi; Abdul Aziz, Maheran; Hasim, Tarmizi (Universiti Putra Malaysia Press, 1994)
The effects of water availability on durian clones D24, D99 and MDUR79 were investigated in two different experiments. In the first experiment, plants were exposed to different water availability: 80%; 40% and 10% of the field capacity. Water deficit reduced vegetative growth, water status and rate of photosynthesis in the plants. There was evidence of clonal effect on photosynthesis rate where clone D99 showed higher photosynthesis values than clone D24. In the second experiment, plants of D24, D99 and MDUR 79 were exposed to a duration of water stress ranging from 7 to 21 days. Plant water status and photosynthesis rate were more reduced by water deficit in the D24 than D99 or MDUR79. Higher proline accumulation in D99 and MDUR 79 clones suggested that both clones were more tolerant to water stress than clone D24.